2020
DOI: 10.1017/s0007114520001154
|View full text |Cite
|
Sign up to set email alerts
|

Methionine-balanced diets improve cattle performance in fattening young bulls fed high-forage diets through changes in nitrogen metabolism

Abstract: Ruminants fed high-forage diets usually have a low feed efficiency, and their performances might be limited by methionine (Met) supply. However, the INRA feeding system for growing cattle does not give recommendation for this amino acid (AA). This study aimed to assess the effects of Met-balanced diets on animal performance and N metabolism in young bulls fed high-forage diets formulated at or above protein requirements. Four diets resulting from a factorial arrangement of two protein levels (Normal (13·5 % cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
(98 reference statements)
2
12
0
Order By: Relevance
“…As previously reported 14 , the RFI differences between Low and High-RFI animals averaged 1.48 kg DMI. Accordingly, the daily intake of organic matter, crude and metabolizable protein, neutral detergent fiber and net energy were also lower (− 13 % on average, P < 0.01) for Low- versus High-RFI animals, irrespective of diet (Table 1 ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As previously reported 14 , the RFI differences between Low and High-RFI animals averaged 1.48 kg DMI. Accordingly, the daily intake of organic matter, crude and metabolizable protein, neutral detergent fiber and net energy were also lower (− 13 % on average, P < 0.01) for Low- versus High-RFI animals, irrespective of diet (Table 1 ).…”
Section: Resultssupporting
confidence: 84%
“…The average daily gain (ADG) of each animal was calculated as the slope of body weight regressed on time. Ultrasound echography (Easi-Scan, BCF Technology Ltd., Vienne, France; equipped with a linear probe) was conducted in three different anatomical regions at end of the RFI test as previously described 14 . Distances analyzed from each anatomical place were the skin (D0) and back fat thickness (D1) that include both subcutaneous tissues and skin.…”
Section: Methodsmentioning
confidence: 99%
“…Amino acid content is an important indicator for judging the protein nutrition of roughage. Protein content and composition can directly affect the growth of the cattle [27] and can also indirectly affect nitrogen metabolism [28]. Our study showed that the EAA content of SC is the highest, or it can be used as a source of high-quality EAA to adjust the balance of amino acids in the diet.…”
Section: Discussionmentioning
confidence: 75%
“…This is because on one hand, DM intake and N intake correlate positively at the individual level even if feed sorting occurs (Dykier et al, 2020). On the other hand, BW gain and N retention are highly correlated since protein and the associated water retention may account for 55-75% of the BW gain in growing-fattening cattle (estimations from values reported in Geay, 1984 andCantalapiedra-Hijar et al, 2020a). The theoretical association between feed efficiency and NUE has been empirically confirmed in dairy cows with contrasted RFI values (Liu and Van de Haar, 2020) and in beef cattle ranked according to FCE (Nasrollahi et al, 2020).…”
Section: The Ability Of N Isotopic Fractionation Vs Plasma Urea To Reflect Dietary and Between-animal Variation In Feed Efficiencymentioning
confidence: 95%